1.Doprowadz wyrazenie do najprostrzej postaci:
a) -(x+5)(2x+y-3)+(4x-2y)(x-y+3)-2(x² +y² )=

2. Wykonaj działania:
a) (2x+y)(x-3y)-x² =
b) -2y²+(-2y+x)(x+5y)=
c) 4x-(4x+y)(1-2y)=
d) (1+y-3x)(y+x)=
e) (3x+2y+1)(2x-y)=
f) (4y-3x)(4+3y+5x)=


bardzo prosze o pomoc:(

1

Odpowiedzi

Najlepsza Odpowiedź!
2009-12-05T20:49:55+01:00
1a
=-(2x²+xy-3x+10x+5y-15)+(4x²-4xy+12x-2xy+2y²-6y)-2x²-2y²=-2x²-xy+3x-10x-5y+15+4x²-4xy+12x-2xy+2y²-6y-2x²-2y²=-7xy+5x-11y+15
2
a=2x²-6xy+xy-3y²-x²=x²-5xy-3y²
b=-2y²+(-2xy-10y²+x²+5xy)=-2y²-2xy-10y²+x²+5xy=x²-12y²+3xy
c=4x-(4x-8xy+y-2y²)=4x-4x+8xy-y+2y²=2y²-y+8xy
d=y+x+y²+xy-3xy-3x²=y²-3x²+x+y-2xy
e=6x²-3xy+4xy-2y²+2x-y=6x²-2y²+2x-y+xy
f=16y+12y²+20xy-12x-9xy-15x²=12y²-15x²-12x+16y+11xy